Effect of geometric variation and solar flux distribution on performance enhancement of absorber tube thermal characteristics for compound parabolic collectors. (July 2023) - Santosh, R.; Kumaresan, G.; Pon Pavithiran, C.K.; Mathu, P.; Velraj, R.
Abstract: A compound parabolic collector (CPC) is a concentrated solar thermal technology widely used for thermal energy storage and electricity generation. Usage of proficient absorber tube configuration improves its thermal efficiency and the present study is an attempt to numerically evaluate the feasibility of employing elliptical absorber tube design in CPCs. Initially, the thermal characteristics of the conventional circular and proposed elliptical absorber tube configurations were evaluated for an ideal condition, taking into account the solar radiation effect from Monte-Carlo ray-tracing analysis. The effect of governing factors that include fluid flow rate (0.015–0.05 kg/min), heat flux (1175–1200 W/m 2 ), and inclination angle (3°) were analyzed for optimum condition identification delivering maximum efficiency. Further analysis was focused on evaluating the thermal loss influence with face-split and top-wall insulation conditions. Results indicated that the elliptical configuration outperformed the circular tube with an increment in the maximum temperature rise by 42.2%, 33.4%, and 27.7% for simple, face-split, and face-split top-wall insulated conditions along with better stability over the local hydrodynamic changes. Face-split analysis contributed to better realistic results over constant heat flux and it was inferred that the inclined face-split elliptical configuration exhibited maximum thermal efficiency with higher temperature rise and nominal pressure drop characteristics.